2018
DOI: 10.3390/met8010077
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Fracture Characteristics of Ti6Al4V Subjected to Ultrasonic Nanocrystal Surface Modification

Abstract: Abstract:The influence of ultrasonic nanocrystal surface modification (UNSM) on the fatigue fracture characteristics of Ti6Al4V was investigated. Two groups of specimens were separated due to different heat treatment conditions. Group one was stress-relief annealed at 650 • C, and group two was then treated with solid solution-aging. UNSM with the conditions of a static load of 25 N, vibration amplitude of 30 µm, and 36,000 strikes per unit produced about 40 µm surface severe plastic deformation (SPD) layers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…It effects the position and the shape of inner crack initiation. It is reported that the high compressive residual stress of TC4 which is treated by UNSM rapidly decreases from the depth of 50 μm to 200 μm [5]. Thus, cracks are initiated easily in this zone without the nanograins and the compressive residual stress.…”
Section: Residual Stressmentioning
confidence: 96%
See 3 more Smart Citations
“…It effects the position and the shape of inner crack initiation. It is reported that the high compressive residual stress of TC4 which is treated by UNSM rapidly decreases from the depth of 50 μm to 200 μm [5]. Thus, cracks are initiated easily in this zone without the nanograins and the compressive residual stress.…”
Section: Residual Stressmentioning
confidence: 96%
“…Noticeably, the inner crack cores are at this zone [35]. In addition, the compressed residual stress decreases quickly, the hardness is closed to the core and plasticity and tenacity are weakened in this area [5]. Therefore, indented slip traces of crystals are obvious in the crack initiation.…”
Section: Fatigue Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cracks in the helix dispenser require the manufacturer to redesign the product to keep it functioning for its expected lifetime. By utilizing the above failure analysis (and tests), fractures that started in voids inside mechanical parts such as gear have been shown to propagate to their ends [23][24][25][26][27][28][29][30]. In particular, intergranular fractures of austenitic stainless steels have been identified and discussed in a similar way to the failure of the helix dispenser [31].…”
Section: Case Study-reliability Design Of the Helix Upper Dispenser Imentioning
confidence: 99%